Alternative Media in Medellín. Trend of issues on its agenda - Valle Florez, Monica María (2020)
In this paper, the trend on the issues that are visible in the alternative media in Medellín is stated. Although the data correspond to a random, non-systematic review of a sample selected at the convenience of the author; it is important to point out that it is the first observation of this agenda, which in the future could promote  lines of research in this regard, and the creation of an observatory of these media, which allows its study and ongoing support for the construction of. By drawing attention to the alternative media agenda, perhaps a third level is being reached in the analysis of these, after their characterization and construction of a public policy that seeks the creation and strengthening of media networks, training, visibility and access of communities to such media alternatives.   It is evident that alternative media are spaces that support, from the local and regional level, citizen awareness, human rights, address and problematize issues of social importance such as drug addiction, inclusion, old age, security, employment, social organization, etc.  Beyond the agenda, there are questions that would enrich studies of this type. Who manage the agendas of the alternative media? Does the agenda of these media coincide with that of the communities in which they are located? Does the agenda of these media have any kind of involvement in other media, governmental instances, community actions, generate public opinion, changes, among others?